Дослідження динаміки змін функціонально-технологічних та структурно-механічних властивостей білково-вуглеводних напівфабрикатів для збитої десертної продукції при зберіганні - Никифоров, Радіон Петрович (НТУ "ХПІ", 2017)
У статті наведено результати дослідження піноутворювальної здатності, стійкості піни, ефективної в'язкості та напруги зсуву в свіжовироблених білково-вуглеводних напівфабрикатах для збитої десертної продукції та при їх зберіганні впродовж трьох діб. Встановлено, що при зберіганні відбувається тиксотропне відновлення структури, зростання ефективної в’язкості зразків, яке призводить до зниження піноутворювальної здатності, стійкості піни та поступового укріплення структури напівфабрикатів.

There are the results of the study of the dynamics of change in functional technological and structural and mechanical properties of protein-carbohydrate semis for whipped dessert products during storage in the article. Currently semis for whipped dessert products have high popularity among consumers. So today many types of this production are developed. The authors are developed albuminous-carbohydrate semifinished item based skim milk, cornelian cherry routine, sloe which does not contain food additives. For determination of its quality it is investigated form froth ability, stability of foam, shear stress, effective viscosity. Form froth ability, stability of foam are determined Lurie traditional method, shear stress, effective viscosity are defined on the device "Rheotest 2". Albuminous-carbohydrate semifinished item is higher values form froth ability, stability of foam than traditional mousse. It is established at storage at 4±2°C for 72 hours there is a growth of the effective viscosity which leads to decrease the form froth ability, stability of foam. It is established that during storage due albuminous-carbohydrate complex formation there is a gradual strengthening of the structure and growth of the initial tension of shift. The results of mathematical processing of experimental data built rheological curves, therefore it is determined that albuminous-carbohydrate semifinished item is nonideal solid plastic body with the maximum tension of shift and begin to flow almost immediately after application of tension. Also at storage there is thixotropic semi restoration of the structure that is confirmed by reduction of the hysteresis loop area.
Study of change of functional and technological, structural and mechanical properties of albuminous-carbohydrate semifinished item for the whipped dessert production at storage
Keywords: знежирене молоко; кизил; терн; піноутворювальна здатність; стійкість піни; напруга зсуву; ефективна в'язкість; білково-вуглеводний напівфабрикат; збита десертна продукція; skim; milk; cornelian cherry; routine; sloe; form froth ability; stability of foam; shear stress; effective viscosity; albuminous-carbohydrate semifinished item; whipped dessert production